Global epidemiological trends of trachea, bronchus, and lung cancer in the elderly - Chen, Jintu; Li, Caili; Yu, Yang; Liu, Shanghai; Hu, Qipeng; Cai, Chengzhi; Luo, Jieyan; Wu, Yijun; Tu, Zegui (Cancer epidemiology, 2025)
Background - Despite most patients with trachea, bronchus, and lung (TBL) cancer being elderly, epidemiological data specific to this population remain scarce. This study aims to update and delineate the global epidemiological profile of TBL in older adults. - Methods - An analysis was conducted on data from the Global Burden of Diseases (GBD) 2021 for individuals aged 60 and older. We evaluated the worldwide impact of TBL cancer by socio-demographic index (SDI), gender, and age across 204 countries and territories, including their spatial and temporal trends. The main outcomes comprised age-standardized incidence rates (ASIR), mortality rates (ASMR), disability-adjusted life years (DALY) rates (ASDR), and average annual percent change (AAPC). - Results - From 1992 to 2021, the estimated cases of TBL cancer, along with associated deaths and DALYs, increased among the elderly. The ASIR, ASMR, and ASDR all exhibited a declining trend. In 2021, East Asia faced a substantial TBL cancer burden, whereas Western Sub-Saharan Africa exhibited a notable increase over the last thirty years. In 2021, Monaco and Greenland recorded the highest ASIR, ASMR, and ASDR, while Egypt experienced the most significant rise in these rates from 1992 to 2021. The greatest affected age group was those aged 85-89. The TBL cancer burden followed distinct patterns by SDI and sex, with higher SDI regions and females facing a particularly notable increase in burden. From 1992 to 2021, smoking was the leading risk factor for TBL cancer-related deaths and DALYs in older adults, with particulate matter air pollution as a close second. - Conclusions - The burden of TBL cancer varies widely across different regions and demographics. More attention should be paid to the elderly in higher SDI regions and females. Recognizing these trends is crucial for enhancing tertiary prevention strategies for TBL cancer and exploring innovative approaches to diagnosis and treatment.